CCS2, an Octatricopeptide-Repeat Protein, Is Required for Plastid Cytochrome c Assembly in the Green Alga Chlamydomonas reinhardtii - Cline, Sara G.; Laughbaum, Isaac A.; Hamel, Patrice P. (Frontiers in Plant Science, 2017)
In bacteria and energy generating organelles, c-type cytochromes are a class of universal electron carriers with a heme cofactor covalently linked via one or two thioether bonds to a heme binding site. The covalent attachment of heme to apocytochromes is a catalyzed process, taking place via three evolutionarily distinct assembly pathways (Systems I, II, III). System II was discovered in the green alga Chlamydomonas reinhardtii through the genetic analysis of the ccs mutants (cytochrome c synthesis), which display a block in the apo- to holo- form conversion of cytochrome f and c6, the thylakoid lumen resident c-type cytochromes functioning in photosynthesis. Here we show that the gene corresponding to the CCS2 locus encodes a 1,719 amino acid polypeptide and identify the molecular lesions in the ccs2-1 to ccs2-5 alleles. The CCS2 protein displays seven degenerate amino-acid repeats, which are variations of the octatricopeptide-repeat motif (OPR) recently recognized in several nuclear-encoded proteins controlling the maturation, stability, or translation of chloroplast transcripts. A plastid site of action for CCS2 is inferred from the finding that GFP fused to the first 100 amino-acids of the algal protein localizes to chloroplasts in Nicotiana benthamiana. We discuss the possible functions of CCS2 in the heme attachment reaction.